PENYULUHAN PENGGUNAAN LISTRIK RUMAH TANGGA SECARA AMAN DAN HEMAT DI DUSUN CEMARA, DESA LEMBAR SELATAN, KECAMATAN LEMBAR, KABUPATEN LOMBOK BARAT - Citarsa, Ida Bagus Fery; I Ketut Wiryajati; I Nyoman Wahyu Satiawan; I Made Budi Suksmadana; Supriono; Cipta Ramadhani (Jurnal Pepadu, 2024)
Many people do not understand how to use household electricity safely and economically. The above problems are also experienced by residents in Cemare Hamlet, Lembar Selatan Village, Lembar District, Lombok Barat Regency. To overcome this problem, the solution offered to the residents of Cemare Hamlet is to carry out counselling regarding this matter. This counseling will enable the residents of Cemare Hamlet to understand how to use household electricity safely and economically so that it can support the safety and efficiency of sustainable use of household electricity. On the day agreed between the counselling team and the residents of the hamlet, this counselling was carried out at the house of one of the residents of the hamlet. After most of the residents had attended, the event finally began. The counseling began with remarks from the team of the Department of Electrical Engineering, Faculty of Engineering, Mataram University, followed by counselling and questions and answers regarding the counselling material. Next, a written and verbal evaluation was carried out (because there were residents who were still illiterate) by the counselling team to the hamlet residents. There are 10 questions given, each worth 10 related to the counseling material that was given previously. The results obtained were that 73.33% of participants answered the questions given with a score of fair to very good, while 26.66% of participants answered the questions given with a score of very poor to poor. These results show that this counselling activity has provided knowledge to residents of Cemare Hamlet regarding the safe and economical use of household electricity.